2019
DOI: 10.1038/s41417-019-0134-6
|View full text |Cite
|
Sign up to set email alerts
|

Alkaliptosis: a new weapon for cancer therapy

Abstract: Malignant tumors are one of the major causes of death worldwide, and the development of better treatments is urgently needed. There are many types of cancer treatment, such as surgery, chemotherapy, radiation therapy, immunotherapy, and targeted therapy, that might improve patient outcomes in a genotype-and stage-dependent manner. The main goal of cancer therapy is to inhibit biological capabilities of tumors and eventually eliminate the cancer cells. However, cancer cells are well known to escape apoptosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“… 1 The traditional core types of cancer treatment are surgery, chemo‐therapy, and radiation therapy, which can reduce tumor cell proliferation by inducing cancer cell death. 2 However, accumulating evidence has shown that tumors often relapse and it has been suggested that successful oncotherapy requires prolonged antineoplastic immunity. 3 The field of cancer immunotherapy (CIT) has emerged in recent years and aims to stimulate the body's immune system to create a robust immune response that can kill cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The traditional core types of cancer treatment are surgery, chemo‐therapy, and radiation therapy, which can reduce tumor cell proliferation by inducing cancer cell death. 2 However, accumulating evidence has shown that tumors often relapse and it has been suggested that successful oncotherapy requires prolonged antineoplastic immunity. 3 The field of cancer immunotherapy (CIT) has emerged in recent years and aims to stimulate the body's immune system to create a robust immune response that can kill cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, iron-dependent regulated cell death (RCD), namely, ferroptosis, has drawn increasing attention in the cellular-molecular field of tumours. Less than a decade ago, ferroptosis was introduced as a nonapoptotic RCD distinguished from necroptosis [7], pyroptosis [8], and alkaliptosis [9,10]. In 2012, Dixon et al [11] first demonstrated that in contrast to apoptotic inhibitors, the growth inhibitory effect of erastin on RASmutant cancer cells can be completely antagonized by iron chelators and lipophilic antioxidants relying on a new form of RCD named ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…RCD can be further classified into apoptotic and nonapoptotic cell death that shows different morphological, genetic, and biochemical characteristics [5]. Since resistance to apoptosis is one of the main obstacles to the successful treatment of cancer, there has been a great interest in the development of reagents to trigger various forms of nonapoptotic cell death (e.g., necroptosis [6,7], pyroptosis [8,9], ferroptosis [10,11], alkaliptosis [12,13], and parthanatos [14,15]) to suppress tumor growth. However, similar to the results previously observed in conventional chemotherapy to induce apoptosis, tumor cells still have resistance to targeted nonapoptotic cell death.…”
mentioning
confidence: 99%